Lifeworld and Symbolic Meaning: Reinterpreting Mappaleppek Tinjak Tradition among the Bajoe Muslim Fishermen in Coastal Indonesia - Izudin, Ahmad (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2026)
This study seeks to reinterpret the Mappaleppek Tinjak tradition within the Muslim fishing community of Bajoe Village, South Sulawesi, Indonesia, situating it as a cultural heritage practice intrinsically connected to Islamic theology. Employing a case study methodology, the article utilizes data collection methods including participant observation, interviews, and documentation to develop a comprehensive empirical understanding. The fieldwork reveals that the socio-economic and socio-religious dimensions of the community’s lifeworld are organized across three principal levels of daily life. At the macro level, structural elements such as maritime ecology, Islamic historical context, and the indigenous Punggawa-Sawi economic system constitute the foundational framework. The mezzo level is characterized by collective practices exemplified by the Bapongka tradition, which encapsulates cultural values alongside a dynamic ecological ethic. At the micro level, meaning is constructed through symbolic and spiritual dimensions that reinforce religious observances. These three levels are interwoven through symbolic significations that generate Islamic values including monotheism, obedience, and gratitude. The broader implications of these findings encompass environmental sustainability, cultural preservation, moral economy, and the equilibrium between worldly existence and the hereafter. As a result, this research contributes significantly to the discourse on intangible cultural heritage by integrating an Islamic theological perspective to elucidate the complexities of contemporary Muslim communal life.